Cote d'Ivoire : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2013)
Cote d'Ivoire's government decided on the National Development Plan to give a new impetus to its development policy. This new strategy is based on an ambitious and realistic recovery and development program centered on private and public investment. The institutional monitoring framework for the implementation of the 2012-15 NDP includes five organs working together for a vibrant, sustained, inclusive, and all-embracing economic growth. The total cost of investments arising out of the proactive scenario, 'the Triumph of the Elephant,' stands at 11,076 billion with equal share given to public and private sectors.